Do cytokines play a role in the transition from acute to chronic musculoskeletal pain? - Andrea Ebersberger; Hans-Georg Schaible (Pharmacological Research)
Musculoskeletal pain has a high prevalence of transition to chronic pain and/or persistence as chronic pain for years or even a lifetime. Possible mechanisms for the development of such pain states are often reflected in inflammatory or neuropathic processes involving, among others, cytokines and other molecules. Since biologics such as blockers of TNF or IL-6 can attenuate inflammation and pain in a subset of patients with rheumatoid arthritis, the question arises to what extent cytokines are involved in the generation of pain in human musculoskeletal diseases. In numerous experimental non-human studies, cytokines have been shown to alter neuronal sensitivity in the peripheral and central nociceptive systems. In this review, we addressed the involvement of cytokines in postoperative pain, complex regional pain syndrome, rheumatoid arthritis, osteoarthritis, temporomandibular joint disease, low back pain and fibromyalgia using PubMed searches including meta-analyses of data. There is evidence that certain pro- and anti-inflammatory cytokines are regulated in all of these diseases, often in both acute and chronic disease states. However, within these data, we found a great deal of heterogeneity in the association between cytokine levels and pain. Neutralization of cytokines showed antinociceptive effects in subgroups of patients with chronic pain (e.g., in a proportion of patients with rheumatoid arthritis), but failed to reduce chronic pain in other diseases (e.g., osteoarthritis). More systematic studies are needed to unravel the pathogenic role of cytokines in human musculoskeletal pain, taking into account the disease process and the mechanisms of pain initiation and maintenance.